2006
DOI: 10.1002/biof.5520260304
|View full text |Cite
|
Sign up to set email alerts
|

6‐Gingerol prevents cisplatin‐induced acute renal failure in rats

Abstract: The present study demonstrates the renoprotective potential of 6-gingerol against cisplatin-induced oxidative stress and renal dysfunction in rats. Hence, 6-gingerol has a potential to be used as therapeutic adjuvant in cisplatin nephrotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
37
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 53 publications
(89 reference statements)
5
37
0
Order By: Relevance
“…The interaction of ROS with cellular components may result in damage to biomolecules, including DNA, proteins, and lipids. Cisplatin treatment also induces a significant increase in the activity of calcium-independent nitric oxide synthase in rat kidney and liver tissues, resulting in an increase in serum NO levels as well as in tissue NO formation (40,41). Peroxynitrite, which is generated by the reaction between nitric oxide and superoxide anion, also oxidizes biomolecules.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of ROS with cellular components may result in damage to biomolecules, including DNA, proteins, and lipids. Cisplatin treatment also induces a significant increase in the activity of calcium-independent nitric oxide synthase in rat kidney and liver tissues, resulting in an increase in serum NO levels as well as in tissue NO formation (40,41). Peroxynitrite, which is generated by the reaction between nitric oxide and superoxide anion, also oxidizes biomolecules.…”
Section: Discussionmentioning
confidence: 99%
“…Cisplatin treatment also causes a significant increase in the activity of the calcium-independent nitric oxide synthase (NOS) in rat kidney and liver, leading to an increase in serum NO level as well as in tissue NO formation. 30,31) Peroxynitrite, generated by the reaction between nitric oxide and superoxide anion, oxidizes biomolecules such as DNA, proteins and lipids. In the present study, the oral administration of the licorice extract in combination with the cisplatin treatment prevented the increases in the serum nitric oxide and tissue lipid peroxidation levels, and significantly recovered the tissue GSH level and antioxidant enzyme activities in the cisplatin-treated mice.…”
Section: Discussionmentioning
confidence: 99%
“…This result suggests that the preventive effects of TJ-19 on BLM-induced pulmonary fibrosis, at least in part, can be ascribed to antioxidative potential. The 3D-HPLC data indicated that TJ-19 contains anti-oxidative constituents including catechin, 6-gingerol, and glycyrrhizin, [14][15][16][17] further supporting the above suggestion. However, in addition to ROS, other inflammatory mediators and mechanisms are involved in the development of BLM-induced pulmonary fibrosis, and these may also affect the inhibitory effects of TJ-19 against BLM-induced pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 52%